PLANTAIN (MUSA ACUMINATA) VALUE CHAIN ANALYSIS IN ONDO STATE, NIGERIA - Similoluwa ADEWOLE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper analyzed the plantain value chain in Ondo State, Nigeria. It identified the various actors in the plantain value chain and their functions, mapped out the various segments, their linkages and the overall plantain value chain and identified the value added at each segment of the value chain. One hundred and seventy seven respondents were selected using multi-staged sampling technique and interviewed using structured questionnaire, informal interview and observation techniques to obtain the primary used. This was analyzed using functional and analysis. Result from the functional analysis, amongst other characteristics, showed that there were eight major actors or segments in the plantain value chain in Ondo State, Nigeria. They are the input suppliers, farmers, processors, marketers, consumers, transporters, cooperative societies and farmers association. This paper concluded that plantain farming is still lowly mechanised and processing has not been fully developed to explore the various value addition options available in this sector. More value can still be added to the product and more upgrading could still be done in the chain. More actors can also take advantage of the prevalence of plantain in the state. In addition, the government and private research institutions should pay attention to the training needs of the farmers so as to properly harness the comparative advantage that the state has above others states in the production of plantain.